Field evaluation of newly-developed controlled release fertilizer on rice production and nitrogen uptake - Mohammad Mu'az Hashim,; Mohd Khanif Yusop,; Radziah Othman,; Samsuri Abd. Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Implementation of sound fertilizer management in rice cultivation is essential in optimizing productivity and profitability. The use of controlled release fertilizer (CRF) to improve crop production in various cropping systems has been widely explored, with new approaches and materials continually being studied to produce new CRF. A field study was carried out to determine the efficiency of local CRFs on rice production and N uptake using MR220 CL1 rice variety. Ten different types of CRFs consisting of two groups namely biochar impregnated urea (BIU 300-5, BIU 300-10, BIU 700-5 and BIU 700-10) and palm stearin (PS) coated urea with nitrification inhibitors (PS, PS+DMPP-100, PS+DMPP-50, PS+DMPP-150, PS+Cu and PS+Zn) were used as treatments. Plant height, SPAD reading, 1000-grain weight and harvest index (HI) showed significant improvement in rice treated with both biochar impregnated and palm stearin coated urea. With respect to grain yield, BIU 300-10, BIU 700-5, BIU 700-10, PS+DMPP-100, PS+DMPP-50, PS+DMPP-150 and PS+Cu treatments significantly increased rice yield. The CRFs mostly showed significantly higher N uptake in rice, especially in rice grains, however, there was no significant difference among treatments in soil residual ammonium (NH4+-N). The newly-developed CRFs showed huge potential as an alternative for common urea, especially BIU 700-5, BIU 700-10, PS+DMPP-100 and PS+DMPP-50, in increasing rice grain yield. With proper approaches, these CRFs can contribute in improving rice production to provide sufficient food for ever increasing population.